The Transition from Strategic Technology Alliances to Mergers and Acquisitions: An Exploratory Study - Hagedoorn, John; Sadowski, Bert (Journal of Management Studies, 1999)
This paper studies a number of research topics derived from the basic question: do interfirm alliances change into mergers and acquisitions as companies that were previously co‐operating become integrated? The analysis is limited to the group of strategic technology alliances, i.e. those interfirm agreements for which joint technology development or technology sharing is part of the agreement.The paper first explores the literature that refers to the possible transition from strategic technology alliances to mergers and acquisitions. Based on this we formulate a number of hypotheses regarding the change in modes of governance and several dimensions of this process related to the international distribution of transformed alliances, their industry specificity, the size of firms, and the distribution of contractual and equity agreements. The major finding of our research is that the transformation from strategic technology alliance to merger and acquisition hardly ever takes place. This suggests that alliances and mergers and acquisitions are not part of a rather smooth continuum but they are first of all different modes of governance where one mode certainly does not lead to the other